Medicines from nature - Thomas, Peggy (New York Twenty-First Century Books, 1997)
Discusses how we have learned from traditional healers around the world about the medicinal value of substances from nature.
Keywords: Pharmacognosy -- Juvenile literature; Ethnobotany -- Juvenile literature; Herbs -- Therapeutic use -- Juvenile literature; Drugs; Traditional medicine; Ethnobotany